CORRELATION OF SST AND CAPE TO RAINFALL IN WEST JAVA AND DKI JAKARTA - Berimah, Azizah Putri; Irfan, Muhammad; Akhsan , Hamdi; Suhadi, Suhadi (EduFisika: Jurnal Pendidikan Fisika, 2025)
High climate variability in the West Java and DKI Jakarta regions is influenced by both local and global factors, particularly Sea Surface Temperature (SST) and Available Convective Potential Energy (CAPE). This study identifies CAPE as a physical mediator between SST anomalies and extreme rainfall, a relationship not previously quantified in local research. Using 40 years of data (1985–2024), the study analyzed correlations among SST, CAPE, and rainfall by integrating ERA5 reanalysis data with rainfall observations from six BMKG stations. The methods included climatological analysis, anomaly evaluation, and Pearson correlation with a significance level of p-value < 0.05. The results show that rainfall patterns follow a tropical monsoon climate, with peak rainfall in December–February and a dry season in June–August. A strong positive correlation between SST and rainfall emerges in southern West Java near the Indian Ocean, whereas in northern areas, such as coastal Jakarta, a negative correlation is observed, influenced by El Niño and a positive IOD. CAPE also shows a strong positive correlation with rainfall at nearly all stations, particularly at Citeko and Kertajati, indicating the dominance of local convective processes. Additionally, SST and CAPE are positively related in the southern region, confirming the role of ocean warming in enhancing atmospheric instability. These findings provide important scientific support for strengthening early-warning systems for extreme weather in densely populated regions.